The Logistics and Politics of the British Campaigns in the Middle East, 1914–22 - Ulrichsen, Kristian Coates. author. aut Link
X, 262 p.
Keywords: An examination of how the logistical demands of the British military campaigns in Palestine and Mesopotamia led to a more intrusive and authoritarian form of imperial control in 1917-18. This early example of Western military intervention in the Middle East provoked a localized backlash in 1919-20 whose effects continue to be felt today.